Integrasi Nilai Islam Dalam PengembanganSains Dan Teknologi Modern - Dalilul Falihin (CV. SINAR HOWUHOWU, 2026)
When it comes to tackling the ethical difficulties brought about by fast technological innovation, the importance of integrating science and Islam in contemporary science and technology is growing. While advancements in science do improve people's lives, they also bring up concerns like moral decay, abuse of technology, and the erosion of spiritual ideals. The rationale, results, and obstacles of combining scientific enquiry with Islamic principles in modern scientific progress are the foci of this research. Data for this study came from current scholarly articles and is based on a qualitative research methodology that makes use of library research. The data is subjected to content analysis in order to extract important themes and patterns about the merging of science and Islam. The findings reveal that integration plays a crucial role in developing a holistic scientific paradigm that combines empirical knowledge with ethical and spiritual values. It also contributes to shaping scientists’ character by enhancing moral awareness, responsibility, and integrity. However, its implementation faces challenges, including persistent dichotomous paradigms, limited interdisciplinary competence, and insufficient integrative resources. In conclusion, integrating science and Islam is essential to ensure that scientific and technological advancements remain ethical, responsible, and beneficial to society.